Makro- in mikrohranila pri zdravljenju osteoporoze - Marc, Janja (Farmacevtski vestnik, 2019)
The porosity of the bone tissue is affected by different factors: gender, age, weight, hormonal status, muscle condition, genetic background and diet. The aim of this paper is to review the macro-and micronutrients, which significantly affect the function of the bone cells and mineralization of the bone collagen. The paper is presenting the biochemical role and results of clinical studies on the impact on bone mineral density and/or osteoporotic bone fractures for four main macronutrients: calcium, vitamin D, phosphorus and magnesium, as well as for four micronutrients: vitamin C, vitamin K, fluorine and zinc. In addition, the adequate intake for described nutrients recommended by the European food safety authority and the Institute of public health of the Republic of Slovenia are presented as well. In conclusion, the intake of the above mentioned macro- and micronutrients is necessary to maintain the quality of bone tissue. However, they are not able to decrease the porosity of bone tissue. There are evidences shown, that theses nutrients can increase the effects of the antiresorptive treatment of osteoporosis with zolendronate or reduce secondary osteoporosis as the adverse effect on bone tissue in other therapies. The positive effects of the micronutrients are stronger if they are taken together, and if they are combined with appropriate physical activity.
Keywords: elementi v sledovih; esencialni elementi; Osteoporoza; povprečne potrebe; Vitamini